2014
DOI: 10.1016/j.exphem.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The BALB/c-specific polymorphic SIRPA enhances its affinity for human CD47, inhibiting phagocytosis against human cells to promote xenogeneic engraftment

Abstract: It has been shown that in xenotransplantation of human cells into immunodeficient mice, the mouse strain background is critical. For example, the nonobese diabetic (NOD) strain is most efficient, the BALB/c is moderate, and the C57BL/6 is inefficient for human cell engraftment. We have shown that the NOD-specific polymorphism of the signal regulatory protein-alpha (Sirpa) allows NOD SIRPA to bind human CD47, and the resultant "don't eat me" signaling by this binding prevents host macrophages to engulf human gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…It was demonstrated that human CD47 minimally binds to SIRPα from either BALB/c, 129 or C57BL/6 mice . In contrast, human CD47 can strongly bind to SIRPα from NOD mice . Indeed, the specific binding of a recombinant human CD47‐Fc fusion protein to BMDM from DKO mice (129/BALB/c mixed background) was minimal and only observed at the high concentration of the recombinant protein (Figure , right panel).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was demonstrated that human CD47 minimally binds to SIRPα from either BALB/c, 129 or C57BL/6 mice . In contrast, human CD47 can strongly bind to SIRPα from NOD mice . Indeed, the specific binding of a recombinant human CD47‐Fc fusion protein to BMDM from DKO mice (129/BALB/c mixed background) was minimal and only observed at the high concentration of the recombinant protein (Figure , right panel).…”
Section: Resultsmentioning
confidence: 98%
“…The CD47‐SIRPα interaction has also been demonstrated to function as an inhibitory signal for phagocytosis of cancer cells by macrophages . It was also demonstrated that human CD47 can nicely bind to SIRPα from nonobese diabetic (NOD) mice, whereas it minimally interacts with SIRPα from either BALB/c, 129 or C57BL/6 mice . Such a difference between mouse SIRPα subtypes for their binding abilities to human CD47 is likely attributable to amino acid variations in the N‐terminal Ig‐V domain of SIRPα .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, a comparison of the expression levels and functional abilities of macrophage inhibitory ligands and in the NSG versus 129 strains has not been performed. However, there is evidence of mouse strain differences in the binding of the ability of the NOD, BALB/s, and B6 forms of SIRP α to bind to the human macrophage inhibitor receptor CD47 and prevent phagocytosis of xenogeneic cells in mice [53]. Our observations that ESHPs are phagocytosed by host macrophages in vitro and that clodronate treatment promotes higher donor chimerism from ESHPs in mice in vivo strongly suggest that ESHPs stimulate innate immune responses and that control of macrophage-induced immune rejection should be considered in the field as new hematopoietic derivatives are produced from ESCs or ESC-like induced pluripotent stem cells for in vivo transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c may possibly be such a candidate (22). It may be necessary to investigate and compare the affinities between human CD47-SIRPα and human CD47-Sirpα BALB/c , which would help determine whether BRG (BALB/c-Rag2 null Il2r γ null ) animal would be a better substitute for NSG as the xenograft host for the study of human CD47.…”
Section: Perspective On Other Applicable Animal Modelsmentioning
confidence: 99%